Networked Human, Network's Human: Humans in Networks Inter-Asia. Issue 4 (1st December 2018) - Kerr, Eric; Graham, Connor; Montoya, Alfred
Abstract: This special issue explores the conceptions of the human that emerge out of the form and the design of information and communications technologies (ICTs). Geographically, our focus compares two countries with a relatively high level of ICT penetration—South Korea and Singapore—and two countries with a relatively low level—India and Vietnam. In each country we see how different forms of the human emerge, in part out of the ways in which technological infrastructure develop and intertwine with social order. In this introduction we reflect on the long genealogy of "human" and "humanity" and the more recent history of ICTs in Asia.